Molecular insights into the effect of hydrocarbon gas composition characteristics on tight oil migration - Yingnan Zhang; Xiangji Dou; Wenteng Zhou; Chang Lu (Scientific Reports)
Abstract Developing unconventional reservoirs through gas injection has become increasingly popular in recent years. Among the various injector gases, hydrocarbon gas is considered one of the most promising fluids for use in the EOR process. In this study, molecular dynamics simulations have been utilized to generate insights into the tight oil migration under six different hydrocarbon gas composition ratios. Simulation results indicate that the migration process of the oil-gas mixture occurs in stages, but the overall states of all systems remain relatively consistent. As the proportion of heavy components (ethane and propane) in the hydrocarbon gas increases, the threshold migration resistance of each system exhibits a pattern of initially decreasing and then increasing. The mechanism underlying the nonlinear evolutionary trend of migration resistance was clarified through analyzing dynamic interactions and interfacial tension characteristics. The essence lies in the fact that the hindrance effect caused by increasingly stronger oil/gas-pore interactions eventually outweighs the drag reduction effect induced by the gradual reduction of oil/gas-water interfacial tension. Based on migration characteristics and sensitivity factors, we propose that the optimal hydrocarbon gas composition ratio for methane/ethane/propane is in the range of 80/10/10 to 70/15/15. Overall, this study focuses on employing molecular dynamics simulations to analyze the oil-gas migration characteristics at the nanoscale, aiming to provide more detailed insights for microscopic analysis and theoretical support for tight oil development.